A study on the modernity and nationality of Chinese piano creation from 1900 to 1949 - Ding, Jiayu (Transactions on Social Science, Education and Humanities Research, 2024)
In 1919, with the outbreak of the May Fourth New Culture Movement, Luting He and Yuanren Zhao began to adapt and create piano music with Chinese musical characteristics. Therefore, this article divided the development of Chinese piano creation from 1900 to 1949 into the embryonic stage (1900-1919), the exploration stage (1920-1935), and the development stage (1936-1949). Taking piano works from different stages as cases, it summarizes the characteristics of Chinese piano composition in various periods, aiming to illustrate how Chinese musicians embraced, adapted Western musical elements, and utilized local musical elements. Furthermore, it explores the modernity and nationality of Chinese piano composition from 1900 to 1949.